2012
DOI: 10.1063/1.4754861
|View full text |Cite
|
Sign up to set email alerts
|

Electro-optic chirality control in MgO:PPLN

Abstract: The chirality of MgO-doped periodically poled lithium niobate (MgO:PPLN) by electro-optic effect was studied. It shows that optical propagation is reciprocal in MgO:PPLN under a transverse electric field and quasi-phase-matching condition, which bears similarity to natural optically active material like quartz. The specific rotation is shown to be proportional to the transverse electric field, making large polarization rotation in optically active material with small size possible. We also demonstrate that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In our previous study, we showed that optical propagation is reciprocal in PPLN by the EO effect, which bears similarity to natural optical activity [22]. Light rotates in the same sense during the forward and backward pass in PPLN, and optical rotation accumulates little for the reflected light, not contributing to optical isolation.…”
Section: Theoretical Analysismentioning
confidence: 59%
See 1 more Smart Citation
“…In our previous study, we showed that optical propagation is reciprocal in PPLN by the EO effect, which bears similarity to natural optical activity [22]. Light rotates in the same sense during the forward and backward pass in PPLN, and optical rotation accumulates little for the reflected light, not contributing to optical isolation.…”
Section: Theoretical Analysismentioning
confidence: 59%
“…In these cases, however, apparent isolation occurs only for a restricted photon state in the backward pass and not for an arbitrary backward incident state. On the other hand, in addition to the Faraday media, there exist numerous optically active materials, such as quartz and periodically poled lithium niobate (PPLN) [22], where optical rotation of light can occur, but not optical isolation. This is because in these materials light rotates in the same sense in the forward and backward pass, and therefore there is no optical rotation accumulation after a round trip through the medium.…”
Section: Introductionmentioning
confidence: 99%
“…Periodically poled LN (PPLN) has been applied to quasi‐phase‐matched NLO wavelength conversion devices [1]. Moreover, it has been applied to EO devices such as Bragg deflection type modulators [2–4] and polarisation conversion type modulators [5–8]. EO polarisation conversion type modulators have been widely studied for various applications [5–8] since they have high efficiency, narrow wavelength bandwidth, a simple electrode structure and a compact optical system.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been applied to EO devices such as Bragg deflection type modulators [2][3][4] and polarisation conversion type modulators [5][6][7][8]. EO polarisation conversion type modulators have been widely studied for various applications [5][6][7][8] since they have high efficiency, narrow wavelength bandwidth, a simple electrode structure and a compact optical system. In addition, wavelength selective modulation and multi-channel modulation for applications such as wavelength division multiplexed networks and multi-colour displays can be realised by cascading a number of modulators with slightly different periods.…”
mentioning
confidence: 99%
“…We have previously proved that the periodically poled lithium niobate (PPLN) with an even number of domains (EPPLN) shows optical activity similar to an optically active medium such as quartz [11] by the transverse electro-optic (EO) effect under the quasi-phase-matching (QPM) condition. However, it will be a different case in PPLN with an odd number of domains (OPPLN).…”
Section: Introductionmentioning
confidence: 99%